Cellular effects and metabolic stability of N1-cyclic inosine diphosphoribose and its derivatives - Kirchberger, T (Nature Publishing Group, 2006)
BACKGROUND AND PURPOSE: Recently, a number of mimics of the second messenger cyclic ADP-ribose (cADPR) with replacement of adenosine by inosine were introduced. In addition, various alterations in the molecule ranging from substitutions at C8 of the base up to full replacement of the ribose moieties still retained biological activity. However, nothing is known about the metabolic stability and cellular effects of these novel analogues. EXPERIMENTAL APPROACH: cADPR and the inosine-based analogues were incubated with CD38, ADP-ribosyl cyclase and NAD-glycohydrolase and metabolism was analysed by RP-HPLC. Furthermore, the effect of the analogues on cytokine expression and proliferation was investigated in primary T-lymphocytes and T-lymphoma cells. KEY RESULTS: Incubation of cADPR with CD38 resulted in degradation to adenosine diphosphoribose. ADP-ribosyl cyclase weakly catabolised cADPR whereas NAD-glycohydrolase showed no such activity. In contrast, N1-cyclic inosine 5′-diphosphoribose (N1-cIDPR) was not hydrolyzed by CD38. Three additional N1-cIDPR analogues showed a similar stability. Proliferation of Jurkat T-lymphoma cells was inhibited by N1-cIDPR, N1-[(phosphoryl-O-ethoxy)-methyl]-N9-[(phosphoryl-O-ethoxy)-methyl]-hypoxanthine-cyclic pyrophosphate (N1-cIDP-DE) and N1-ethoxymethyl-cIDPR (N1-cIDPRE). In contrast, in primary T cells neither proliferation nor cytokine expression was affected by these compounds. CONCLUSIONS AND IMPLICATIONS: The metabolic stability of N1-cIDPR and its analogues provides an advantage for the development of novel pharmaceutical compounds interfering with cADPR mediated Ca(2+) signalling pathways. The differential effects of N1-cIDPR and N1-cIDPRE on proliferation and cytokine expression in primary T cells versus T-lymphoma cells may constitute a starting point for novel anti-tumor drugs.